Perbandingan istilah pinjaman bahasa Melayu dan bahasa Korea (Jurnal Bahasa, 2022)
This study attempts to trace the similarities and differences in the translations of foreign terms into the Malay and Korean language. The study also examined the method of forming a term that is applied in both languages. The research data consists of a term often used by the general public in the field of medicine and banking. Data from related field are collected from newspapers, brochures for the public, and the Malay language corpus database. Data are then compared with the terms in Korean which are obtained through the questionnaires given to the Korean informants. The study describes the phenomenon of borrowing foreign words through the translation of terms in both languages thus contribute to the process of language planning.